MADRASAH: QUALITY AND SOCIAL CHANGE (Case Study in Banjarmasin Indonesia) - Ahdi Makmur; M. Arrafie Abduh; Hasbullah Hasbullah; arridho abduh (AL-FIKRA, 2021)
According to Indonesian Constitution of 1945, every citizent has his/her right to get education. Consequently, Indonesian government has to provide educational institutions for its nation, like school, madrasah and other forms of non-formal education. Both school and madrasah are carried out in different management. School management is on the hands of the Manistry of Education and Culture, madrasah is managed under the responsibility of the Ministry of Religious Affairs. The difference, however, presents dualism of educational system in Indonesia. As the result, madrasah has no more progress, treated discriminatively, and marginalized.  What a negative action it has, nowadays madrasah still exists in this country.  The purpose of this article is to explain the quality of madrasah (plural: madrasahs) and their role as the agent of social change. This is a field research of qualitative-quantitative approach carried out in a provencial capital city, that is Banjarmasin in South Kalimantan Indonesia. The madrasahs studied were 15 (n=15) with various levels and status including the founding organizations that are responsible. The data were collected by questionaire, interview, observation and documentary.  By measuring the eight indicators of National Education Standard consisting of content standard, process, outputs, teachers and non-educational staff, structures and infrastructures, management, cost, and standard of assesment, it is finally concluded that the quality of madrasahs was very good, although a little difference found out among the educational levels of them, between the state and private madrasahs. In addition, by understanding the students mind set, value, belief, norm, behaviour and their moral or ethics, madrasahs also have played the role  largerly and significantly in social change, except in some aspects which have been deeply rooted in their tradition like their belief on supernatural life, sacrality and irrational power, that basically have not changed yet.